2006
DOI: 10.1111/j.1399-3046.2006.00601.x
|View full text |Cite
|
Sign up to set email alerts
|

Vascular complications in living‐related and deceased donation pediatric liver transplantation: Single center's experience from Turkey

Abstract: The aim of the study was to assess early and long-term incidence of venous complications, in both deceased donation (DD) and living-related (LR) liver transplantation (LT) in a pediatric population. Seventy-five liver transplants performed in 69 (39 boys, 30 girls) children at Ege University Hospital between 1997 and 2004 were prospectively monitored and reviewed. Age, sex, primary diagnosis, graft type, vascular complications and their management were evaluated. All patients received Doppler ultrasonographic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
47
3
2

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(54 citation statements)
references
References 17 publications
1
47
3
2
Order By: Relevance
“…They can be potentially devastating and lead to graft failure, and therefore represent an important source of morbidity and mortality after OLT, especially if they occur in the early postoperative period [9,90,91] . Numerous literature reports have demonstrated that the incidence of venous complications in pediatric transplants is higher than in adult transplants [9,62,92,93] . Venous complications following OLT include: Portal (1%-3%) and caval (< 2%) problems [5,8,9,91] .…”
Section: Venous Complicationsmentioning
confidence: 99%
“…They can be potentially devastating and lead to graft failure, and therefore represent an important source of morbidity and mortality after OLT, especially if they occur in the early postoperative period [9,90,91] . Numerous literature reports have demonstrated that the incidence of venous complications in pediatric transplants is higher than in adult transplants [9,62,92,93] . Venous complications following OLT include: Portal (1%-3%) and caval (< 2%) problems [5,8,9,91] .…”
Section: Venous Complicationsmentioning
confidence: 99%
“…Continuity of the mass with the hepatic artery which is isoattenuating to the aorta during the arterial phase is the key for the correct diagnosis, as it was in our case. Angiography is not only the gold standard in the diagnosis of HAA, but also serves as a guide for theraupeutic embolization in suitable cases [1,5,6]. Because of lack of an interventional angiographic unit at our institution, angiography could not be performed in the present case.…”
Section: Discussionmentioning
confidence: 95%
“…Less common causes for HAA are vasculitis, such as polyarteritis nodosa, periarterial inflammation caused by either cholecystitis or pancreatitis, fibromuscular dysplasia, and cystic medial necrosis [4,5]. Moreover, HAA are among the anastomotic complications of liver transplantation [6]. The presentation of HAA is acute and catastrophic.…”
Section: Discussionmentioning
confidence: 99%
“…Ou (2011) [91] Taiwan R/C LDLT, BA 0-20 Not described PVT 7.6% Pape (2004) [57] Germany R/C KT 0-18 UFH GT 1% Perito (2014) [92] North America R/C LT, UCD/OA 0- [96] Netherlands R/C LT 0-18 ASA in selected cases HAT 10%, PVT 4% Singh (1997) [97] North America R/C KT 0-18 Not examined GT 1.8% (LD) vs. 4.2% (DD) Smith (2006) [98] North America R/C KT 0-18 Not examined GT 1.9% Smith (2013) [45] North America R/C KT [100] North America R/C LT 0-18 Not described PVT 3.7% Wessel (2013) [34] Multinational RCT S-PA shunts < 3 month ASA vs. ASA+clopidogrel Shunt thrombosis 20.5% vs. 19.1% Wolf (1997) [20] USA R/C LT All UFH (< 6 year), ASA HAT 9.1-15.8% (< 12 year), 3.2% (> 12 year) Yilmaz (2007) [101] Turkey P/C LT 0-18 ASA HAT 6.7%, PVT 8.7%…”
Section: Thromboprophylaxismentioning
confidence: 99%